Financialisation of the Maltese household? Household debt dynamics, the mortgage market, and housing in Malta - Dylan Cassar (Central Bank of Malta, 2023)
This paper provides a comprehensive assessment of household debt dynamics in Malta between 2010 and 2020. Drawing on the Household Finance and Consumption Survey, it argues that a process of financialisation of the household is underway on the Maltese islands, primarily via the mortgage market. This process is characterised by (i) financial extension, in which more households partake in mortgage finance in their entry to homeownership, and (ii) financial intensity, in which households accumulate more debt in accessing the property market. In explaining this process, I claim, firstly, that mortgage finance represents an 'alternative' channel to older dominant institutional entryways to homeownership. Secondly, Maltese households are engaging in financial intensification in order to stretch their purchasing power in the property market, and possibly to maintain a standard of living comparable to older generations'. While this is the case for the average Maltese household, results point to some heterogeneity across different households, as younger and lower-income households are relatively more indebted, though the latter are also being driven out of the property market in the context of rising property prices. The paper sets out a novel agenda for scholarship in the Maltese context, namely to put under scrutiny the increasingly central place of finance in Maltese society.
Keywords: Z13; G5; D1; 330; household debt; financialisation; mortgage market; housing; homeownership